Bacterial diversity in sediments from lakes of the Byers Peninsula (Livingstone Island, Maritime Antarctica) as determined by next generation sequencing - LO GIUDICE, ANGELINA; MICHAUD, LUIGI; GUGLIANDOLO, Concetta; LENTINI V.; MOCCIARO C.; CAMACHO A. RAPPAZZO A. C.; ROCHERA C.; RIZZO C. (2014)
Byers Peninsula, one of the largest ice-free area of Maritime Antarctica, includes a large number of lakes showing relatively heterogeneous ecological conditions, especially referring to their morphology (shallow vs moderately deep) and trophic status, from ultra-oligotrophic to oligotrophic in inland lakes and eutrophic in coastal lakes, due to the input of organic matter from marine animals. Previous studies revealed that Bacteria always dominated over Archaea in sediments from these lakes. The aim of the present study was to evaluate the community structure and composition of Bacteria associated with lacustrine sediments by using 454 tag pyrosequencing of the V3-V4 16S rRNA gene region. Sediment samples were collected during the 2008-2009 Austral summer, from five inland lakes, two coastal lakes and from an estuarine site. Distinct bacterial populations were detected in each sediment sample. Lacustrine sediments were more phylum rich than the estuarine sediment, and the dominant groups (relative abundance ≥1% of total reads) were Proteobacteria (mainly composed by Beta- and Alpha -proteobacteria), Actinobacteria, Acidobacteria, Verrucomicrobia and Gemmatimonadetes. In contrast, Proteobacteria (mainly composed by Gammaproteobacteria), Bacteroidetes and Firmicutes were the dominant groups in the estuarine sample. Cyanobacteria, which are the main components of Byers’ microbial mats covering vast inland extensions, were more abundant in the inland than in coastal lakes, while they were rarely (<1%) represented in the estuarine sample. Bacterial diversity at genus level was higher in inland than in coastal lakes. Ilumatobacter (Actinobacteria), Gp16 (Acidobacteria) and Gemmatimonas (Gemmatimonadetes) were recovered as dominant genera in lacustrine sediments, but not in the estuarine sample. Comparisons of the bacterial diversity with environmental features show that the trophic conditions of the lakes greatly influence sediment community composition.